If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(x+2)=-5-2(x-4)
We simplify the equation to the form, which is simple to understand
3(x+2)=-5-2(x-4)
Reorder the terms in parentheses
+(+3x+6)=-5-2*(x-4)
Remove unnecessary parentheses
+3x+6=-5-2+*(+x-4+)
Reorder the terms in parentheses
+3x+6=-5+(-2x+8)
Remove unnecessary parentheses
+3x+6=-5-2x+8
We move all terms containing x to the left and all other terms to the right.
+3x+2x=-5+8-6
We simplify left and right side of the equation.
+5x=-3
We divide both sides of the equation by 5 to get x.
x=-0.6
| 25-39=11 | | 6X+19X-7=5(5X+5) | | -0.75=-0.6+s | | -2.4x=-2.88 | | 5x+28(x-2)=406 | | x-5x=7x-9x-x | | X+0.375=-1.75 | | -328=-56b+7 | | -5+4r=-5r+4r | | 19-13p=-5-17p | | 0.5+0.5j=0 | | ln(5X+1)=4.5 | | 3x+12=7x-22 | | x+3(x-3)=91 | | 2x=-16+4y | | 3x-66=9x | | 1+k=3k-1 | | -0.6+y=-0.33 | | -28=v-18 | | 20+18x-2=21x | | X-9.2=-4.55 | | 4=p-1 | | X-1.25=3.5 | | 0.5-0.5j=0 | | 2(h+3)+1=9 | | 0=-9(b-1) | | x^2+3-12=0 | | 12x^3-8x^2-35x+6=0 | | (2x+4)(x)=20 | | X+0.3=-0.4 | | -6.75=x+5.4 | | 4(2x+4)=10x+15-2x+17 |